Deconstructing the Risk and Return Profile of Penny Stocks: Evidence from the Market Model - Hendri Sembiring; Rexon Nainggolan (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study investigates the risk and return profile of penny stocks on the Indonesia Stock Exchange (IDX), focusing on abnormal returns, systematic risk, and idiosyncratic volatility (STEY X). Research Methodology: Using a sample of 600 listed firms in 2024, the study applies the Market Model and several robust statistical analyses include Welch’s t-tests, Mann–Whitney U tests, Levene’s test, and variance decomposition to assess differences across groups. Results: The findings show that penny stocks on the IDX have a paradoxical risk-return profile. They significantly underperform non-penny stocks with a negative abnormal return 6.13 times larger, but carry 22.15% less systematic risk (beta). This low market sensitivity suggests these stocks are decoupled from broader market movements. Instead, they are driven by intense idiosyncratic risk, which is 54.7% higher than that of non-penny stocks. Consequently, while penny stocks are less sensitive to the general market, they are much more volatile due to firm-specific factors. Conclusions: The results confirm a breakdown of the traditional risk–return paradigm in the IDX penny stock segment, characterized by a beta paradox and dominance of idiosyncratic risk. High volatility is not compensated by higher returns, reflecting speculative trading and structural inefficiencies. Limitations: The study is limited to a single year of data and focuses solely on the Indonesian market, which may restrict generalizability. Contributions: This research contributes to emerging market finance by highlighting market segmentation effects, questioning the universal applicability of CAPM, and providing empirical evidence on the dominance of idiosyncratic risk in low-priced equities.